COMPANY PERFORMANCE APPRAISAL USING THE BALANCE SCORECARD METHOD TO IMPROVE PERFORMANCE IN PUBLIC COMPANIES JASA TIRTA I - Prasetiyo, Supriyadi Eko; Burhan, Mohammad; Apriyanto, Gaguk (FIA UB, 2021)
Jasa Tirta I Public Company is a state-owned company engaged in the management of water resources. The quality of the performance of an organization can be known by measuring the performance of the achievement of performance indicators. Comprehensive planning of performance indicators is needed. This study aims to determine the performance measurement of Perum Jasa Tirta I by the Balanced Scorecard method and then analyzed by the PDCGA (Plan-Do-Check-Goal-Action) method for continuous improvement to improve company performance. The research method used in this study uses a mixed-method approach. The results showed that the measurement of public performance based on the Balanced Scorecard Perum Jasa Tirta I 2015-2019 method is divided into 4 approaches: financial perspective, customer perspective, internal business process perspective, and learning & growth perspective including good performance. Judging from the financial perspective it is included in the very good category. From the customer perspective, it is included in the excellent category. From the internal business perspective it is classified as quite good, Electricity Raw Water Service indicators reached 93% of the 100% target and environmental management achieved 97% of the 100% target. From the perspective of learning & growth in the excellent category.